Safety assessment of the process 'Veroniki Ecogrup SRL', based on Starlinger Decon technology, used to recycle post‐consumer PET into food contact materials. (14th July 2017) - ; Silano, Vittorio; Bolognesi, Claudia; Castle, Laurence; Cravedi, Jean‐Pierre; Engel, Karl‐Heinz; Fowler, Paul; Grob, Konrad; Gürtler, Rainer; Husøy, Trine; Kärenlampi, Sirpa; Mennes, Wim; et al.
Abstract: This scientific opinion of the EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF Panel) deals with the safety evaluation of the recycling process Veroniki Ecogrup SRL (EU register No RECYC0145), which is based on the Starlinger Decon technology. The decontamination efficiency of the process was demonstrated by a challenge test. The input of this process is hot washed and dried poly(ethylene terephthalate) (PET) flakes originating from collected post‐consumer PET containers, mainly bottles, containing no more than 5% of PET from non‐food consumer applications. In this technology, washed and dried PET flakes are preheated before being submitted to solid‐state polycondensation (SSP) in a continuous reactor at high temperature under vacuum and gas flow. Having examined the challenge test provided, the Panel concluded that the preheating (step 2) and the decontamination in the continuous SSP reactor (step 3) are the critical steps that determine the decontamination efficiency of the process. The operating parameters that control their performance are well defined and are temperature, pressure, residence time and gas flow for step 2 and 3. Under these conditions, it was demonstrated that the recycling process under evaluation, using the Starlinger Decon technology, is able to ensure that the level of migration of potential unknown contaminants into food is below a conservatively modelled migration of 0.1 μg/kg food. Therefore, the Panel concluded that the recycled PET obtained from this process and intended to be used up to 100% for the manufacture of materials and articles for contact with all types of foodstuffs for long‐term storage at room temperature is not considered of safety concern. Trays made of this PET are not intended to be used, and should not to be used in microwave and conventional ovens.